Locus of Control dalam Memediasi Pengaruh Financial Knowledge dan Gaya Hidup terhadap Financial Behavior Management Mahasiswa Penerima Beasiswa Iib Darmajaya - Putri, Reisa Dyasvaro Zulanda; Badri, Rico Elhandro; Asnusa, Soraya (J-MAS (Jurnal Manajemen dan Sains), 2024)
The government has allocated the Program Indonesia Pintar (PIP) scholarships to various universities, both public and private, across Indonesia. Each university has a different scholarship quota. In 2022, IIB Darmajaya received a PIP quota of 52. The ease of obtaining desired goods and services to provide momentary satisfaction leads individuals to behave consumptively and irrationally in spending their money on items that do not have beneficial value. Financial literacy and financial inclusion are factors that can influence a person's wise behavior in managing their finances. The aim of this study is to examine the factors of financial knowledge, lifestyle, and locus of control on the financial management behavior of scholarship recipients at IIB Darmajaya. Based on the results of the study, it was concluded that financial knowledge does not affect financial management behavior, locus of control mediates the effect of financial knowledge on financial management behavior, lifestyle affects financial management behavior, and locus of control mediates the effect of lifestyle on financial management behavior among the scholarship recipients at IIB Darmajaya.